Estratégias para administração segura de antineoplásicos - Freitas, Karina Alexandra Batista da Silva [UNESP] (2015)
Introduction. Patients undergoing cancer chemotherapy needs an adequate venous access. As the an intravenous administration is the most used, the peripheral venous access is commonly used and may cause some issues as extravasation. Extravasation consists in an infusion of antineoplastic agents out of the vase causing extensive dermatological local toxicity. They are classified as irritant, not vesicant and vesicant. The prevention of extravasation must be stimulated to ensure the quality of patient care submitted to this treatment. Objective. Make the profile and knowledge of the chemotherapy nurses from inpatient units of a university hospital and develop strategies for safe administration of antineoplastic. Material and methods. Exploratory descriptive research with a quantitative approach, carried out with 30 nurses of a public University Hospital and in São Paulo School. Approved by the Research Ethics Committee of the Medical School of Botucatu / UNESP - Opinion 820,619. The research was conducted in two stages. First were put the knowledge of nurses through a questionnaire with objective questions addressing related content on chemotherapy administration and overflow. The data collection was conducted in November and December of 2014. In the second, it was made strategies for safe administration of antineoplastic that contained labels that include the recommendations of the current literature and provide subsidies for nurses identify the chemotherapy according to its potential to damage a Standard Operating Procedure for intravenous chemotherapy administration and extravasation Manual of antineoplastic agents. Results / Discussion: It was observed that 93% of nurses had no training in chemotherapy, 60% had a low time of Institution not exceeding five years. None of the interviewed had expertise in oncology, only 17% know the difference between chemotherapy by injury potential (irritant, not vesicant and vesicant), although all agree that should be a differentiation through the labels. With the implementation of the products in the study institution, there was a routine change in the administration of chemotherapy, bringing a new concept about the quality of care and patient safety, as recommended in the DRC and 36 of 25.7.2013 desired by the institution. It was provided to the institution nurses a training course about chemotherapy administration. Prepared Products: It were elaborated a Standard Operating Protocol for intravenous chemotherapy administration, different labels to identify the anticancer according to their injury potential (red, yellow and green) and an extravasation Manual of antineoplastic agentes containing a flow chart of the main nursing actions after a leak and its documentation and can be accessed in the form of e-book on the internet and intranet of the institution by the address: www.hcfmb.unesp.br/bibliotecadigital. Conclusion: The extravasation is one of the most serious complications of chemotherapy intravenous treatment. The safe administration of the antineoplastic should be stimulated aiming the patient safety submitted to this therapy. This study enabled the implementation of strategies for safe practice of the administration of antineoplastic agents, as establish a routine for the care of extravasation, whereas the institution strives for quality of care and patient safety.